Structure, microstructure and electrical properties of Tl-2212-silver composite / Faizah Md. Salleh and Ahmad Kamal Hayati Yahya - Md. Salleh, Faizah; Yahya, Kamal Hayati (2001)
Superconductivity was discovered for the first time in 1911.'27J Dutch physicist at the University of Leiden, Kamerlingh Onnes acquired liquid helium at absolute temperature 4K by compressing helium gas. Using this liquid, he found that the electric resistance of Hg abruptly dropped near 4.2 K which is the boiling temperature of liquid helium. It is termed superconductivity that electric resistance does not exits at all. The variation of resistance with temperature for a superconductor and a normal conductor at low temperatures is show in Figure 1.1. The resistance of the superconductor drops abruptly to zero at the critical temperature Tc. The resistance is truly zero, not just merely very small as current induced in macroscopic superconducting materials persist indefinately without any diminution. However, it is known that if a current density, J, larger than the critical current density, Jc, is applied to the superconductor, superconductivity is destroyed.